Pangenome analysis indicates evolutionary origins and genetic diversity: emphasis on the role of nodulation in symbiotic Bradyrhizobium - Terra, Leonardo Araujo; Klepa, Milena Serenato; Nogueira, Marco Antonio; Hungria, Mariangela (Frontiers in Plant Science, 2025)
The Bradyrhizobium genus is widely known for encompassing many species capable of forming nodules and establishing the biological nitrogen fixation process with several legumes, significantly contributing to agriculture and environmental sustainability. Despite its importance, questions about the evolution, pangenome, and symbiotic genes of Bradyrhizobium are still poorly understood. In this study, we analyzed the pangenome of a set of Bradyrhizobium symbiotic species using the Roary and GET_HOMOLOGUES tools in strains originated from the Northern and Southern Hemispheres. We also investigated the presence and correlation of the fix, nif, nod, Type III secretion system (T3SS) and their effector proteins, and T4SS genes, trying to find differences between clades, hosts, and biogeographic origin. Pangenome analysis of Bradyrhizobium species from the Northern and Southern Hemispheres provided valuable insights into their diversity, biogeography, origin, and co-evolution with their legume host plants. The genus possesses a relatively small core genome compared to the expanded accessory genome, a key feature that facilitates genetic exchange and acquisition of new genes, allowing adaptation to a variety of environments. Notably, the presence or absence of T3SS effector proteins varied significantly according to the geographic location, suggesting specific environmental adaptations, as well as a direct relationship with nodulation genes. Comparative analysis indicated that symbiotic Bradyrhizobium species originated in the Northern Hemisphere and present a greater diversity of orthologous groups than those from the Southern Hemisphere. These results contribute to our understanding of the evolutionary history of these symbiotic bacteria.